The Effect of Zinc Nutrition on Two Olive (Olea europaea L.) Cultivars Components and Alleviate Oxidative Damage in Salinity Conditions - Mohammad Reza Naeini; Mahmood Esnaashari; Amir Hossein Khoshgoftarmanesh; Hossein cheraghi; Ashkan Hatami; Mohammad Hadi Mirzapour (Journal of Medicinal Plants and By-products, 2016)
The role of zinc (Zn) in enhancing defense capacity of several plants against salinity has been demonstrated but there is limited information on the impact of Zn nutrition on alleviating salinity-induced oxidative damage in olive. One-year-old seedlings of two varieties of olive (Olea europaea L. cvs. Frontoio and Conservolea) supplied with three Zn levels (0, 1 and 5 mM in the form of ZnSO4.7H2O) were exposed to four salinity levels (0, 40, 80 and 120 mM NaCl). The increase in plasma membrane permeability and elevated leakage of potassium (K) and Zn from the olive roots were considered as indices of oxidative damage caused by salinity on root cells. In contrast, root membrane permeability and leakage of Zn and K ions in plants supplied with Zn was less than those non-supplied with Zn. Addition of Zn resulted in higher activity of CAT and APX. Higher salt-tolerance of Frontoio cultivar was associated with higher concentration of sulfhydryl (-SH) groups and lower membrane permeability of its roots in comparison with Conservolea cultivar. Based on the results obtained, addition of Zn improved plant enzymatic defense system and partly alleviated oxidative injuries induced by salinity on the olive.